Sunday

December 21, 2014

December 21, 2014

Posted by **Amanda** on Saturday, December 1, 2007 at 11:13pm.

4x^3-4x^2+13x-6=0

note: that's suppose to be 4x to the third and 4x squared

- trig -
**Reiny**, Saturday, December 1, 2007 at 11:48pmAfter several tries I found a factor

(2x-1)(2x^2 - x + 6) = 0

x = 1/2 or x = (1 √-47)/4 or (1 i√47)/4

**Answer this Question**

**Related Questions**

Algebra - Can you pleas Solve the quadric equation step by step 4x square =13x+...

intermidate alegbra - Solve each equadratic equation by factoring. 6^2-13x-28 36...

Algebra - Hello all - I would like to check my work on 2 problems. Solve by ...

Math - Solve the following equation. 4.7 = 1.13x^2 Do i square root the 1.13x^2 ...

math - Still looking at how to solve these... Both are cubic polynomials? 43x^3...

MATH/ALGEBRA - SOLVE: (4x+ 5) + 1 = 0 (4x+ 5)= -1 ((4x+ 5))squared= (-1)...

Math - Factor the polynomial P(x)=x^3-2x^2-13x-10. Then solve the equation P(x)=...

math - How do i find the area of a triangle? For example: A squared + b squared...

Algebra - Solve the equation using the Quadratic Formula 5xsquared+13x-6=0 i ...

Pre-Calc - I need to figure out how to solve the equation x-squared y-squared+xy...